Fleet management system - Challa, Abhishek (Kansas State University, 2016)
Web services have become quintessential in web application development. RESTful web services are one way of providing interoperability between computer systems on the internet. REST-compliant web services allow requesting systems to access and manipulate textual representations of web resources using a uniform and predefined set of stateless operations. These services, which are online APIs, can be accessed from various applications and the results can be used to offer specific functionality to users. This project consists of an Android app, a Server application and a Client application. The Server application exposes a REST API (Web Services developed using REpresentational State Transfer (REST) protocol) using, which the consuming client applications can make use of various functionalities as services across the network. The Android app would be installed in the smart phone present in each vehicle of the fleet, this app would send live location data to the database using the REST API. The manager uses the client application to track the vehicles in real time, the manager can also choose to track a particular vehicle. The API could also be used to integrate the services with other systems. This project serves to a wide variety of users, from small local businesses owning tens or hundreds of vehicle to parents who would like to track the location of their children in real time. This project aims to help the managers/owners better control and track the vehicles. Also, the exposed API could be used by other developers to customize or extend this application. This project is easy to install, use and hence friendly for users with even minimal computer skills.
Keywords: Web Services; Hibernate; Spring; Android